A STUDY ON EMPLOYER BRANDING FOR HOSPITALS WITH REFERENCE TO COIMBATORE (Journal of Pharmaceutical Negative Results, 2022)
Hospitals are an unavoidable sector in the modern world, which is pushed by technology, and they are the sector that displays the standing of a country on an international level. Every country's ability to deliver high-quality medical care is an indication of its level of progress toward a brighter future. Therefore, "Employer Branding" for hospitals is something that must be done in order to ensure both higher quality services and continued growth in the health care industry. The technique of building a positive employer brand has shown to be valuable for many kinds of businesses, including hospitals. This, in turn, leads to a means for them to keep their brilliant personnel, which is the fundamental need that any hospital must fulfil in order to achieve a competitive edge. The company has become more competitive as a result of the dynamic development that has taken place in today's competitive globe. In order to thrive in the cutthroat competition brought on by globalization, a business has to find a way to differentiate itself from its competitors and secure a competitive edge. It has to be proactive in order to deal with the shifting circumstances. In this particular case, the organization's human resources are serving as the primary propellants behind its expansion. The success of an organisation is dependent on the quality of work that is accomplished by the workforce. Human resources are the ones who decide, implement, and manage the activities inside a company because of their skills, aptitudes, and attitudes. They are the ones who are the drivers of the organisation. Now is the moment for the organisation to make the move that will put them ahead of their rivals and place them in first place. In light of these circumstances, talent management has emerged as a key instrument for the development of organisations, which should be matched with the growth of individuals.